PERBANDINGAN PENERAPAN MODEL PROBLEM BASED LEARNING DAN PROJECT BASED LEARNING DITINJAU DARI AKTIVITAS BELAJAR SISWA KELAS V GUGUS III KECAMATAN BONTOMARANNU - Fajriah, Nurul Hikmah; Sukmawati; Agustan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study discusses the comparison of the implementation of the Problem-Based Learning (PBL) and Project-Based Learning (PjBL) models in terms of the mathematics learning activities of fifth-grade students in Cluster III, Bontomarannu District. The study aims to determine whether there is a significant difference in the mathematics learning activities of fifth-grade students using the Problem-Based Learning model compared to the Project-Based Learning model.This research is an experimental study using a counterbalanced design. The population in this study consists of all fifth-grade students in Cluster III, Bontomarannu District, while the selected sample includes students from SD Inpres Bonto-Bonto and SD Inpres Balangpapa, totaling 78 students, chosen using the cluster random sampling technique.The data collection technique in this study is observation to assess students' learning activities. The data analysis techniques used are descriptive statistics and inferential statistics. The research findings indicate that the significance value obtained for students' learning activities is 0.038 < 0.05, leading to the conclusion that there is a significant difference in the learning activities of students taught using the PBL model compared to those taught using the PjBL model.